Art Deco Style objects arch, graphic, jewelry - Menten, Theodore (2007)
"Art Deco Style" by Theodore Menten offers a comprehensive exploration of the Art Deco movement, highlighting its distinctive aesthetic and influence across various disciplines, including architecture, graphic design, and jewelry. The book delves into the defining characteristics of Art Deco, such as bold geometric shapes, rich colors, and luxurious materials, while showcasing a wide array of objects and artworks that exemplify this iconic style. Menten discusses key figures in the Art Deco movement, examining how cultural, social, and technological changes of the early 20th century shaped artistic expression. Through detailed illustrations and photographs, the book serves as both a visual catalog and a scholarly examination of the enduring legacy of Art Deco, celebrating its impact on design and aesthetics.
Keywords: Art Deco; Graphics Design; Architecture; Jewelry -- sculpture